Proxies for Basement Structure and Its Implications for Mesoproterozoic Metallogenic Provinces in the Gawler Craton. Issue 3 (7th March 2019) - Motta, J. G.; Betts, P. G.; de Souza Filho, C. R.; Thiel, S.; Curtis, S.; Armit, R. J.
Abstract: The link between mineral resources and crustal‐rooted structures has been proposed for many of the world's most significant mineral provinces. Here we utilize a new approach by interpreting potential field data, including satellite gravity data, and high‐resolution continental‐scale magnetotelluric data, constrained with aeromagnetic, and seismic tomography and reflection data, to determine the distribution of crustal‐scale faults in the Archean to Proterozoic Gawler Craton (South Australia). The eastern flank of the craton hosts the supergiant Olympic Dam iron oxide‐copper‐gold (IOCG) deposit within a larger Olympic IOCG province. The central part of the craton contains gold‐only deposits, which define the Central Gawler Gold province. Both of these provinces are part of a Mesoproterozoic mineral system with an extensive hydrothermal alteration footprint, which formed during complicated tectonic mode switches. We show that both types of mineralization are located in proximity to crustal‐scale structures that appear to connect deep crustal fragments, which likely record the amalgamation of the Archean nucleus of the craton during the Neoarchean with subsequent reworking during the Mesoproterozoic. Many of these structures do not have a surface expression but coincide with gradients in magnetism, gravity, and electric resistivity anomalies, the latter data set suggesting they acted as fluid pathways extending to the lower crust. The results indicate that the first‐order controls on the distribution of IOCG and Central Gawler Gold metallogenic provinces are inherited from earlier tectonic events, which formed major crustal boundaries and related structures that are prone to reworking during later tectonism. Key Points: The satellite gravity data provide clues to the regional framework of the Gawler Craton, which aligns with different geophysical data sets The Gawler Craton is formed by a threefold Archean substratum that has undergone changes in the Proterozoic down to its deep crustal levels Regional structures were reactivated through time and act as pathways for regional fluid flow throughout the craton